Disability, Narrative, and Moral Status - Purcell, Elizabeth B. (Disability Studies Quarterly, 2016)
The present essay aims to respond to recent arguments which maintain that persons with severe cognitive impairments should not enjoy the full moral status or equal dignity as other "cognitively-able" humans. In the debate concerning moral standing and worth, philosophers Singer and McMahan have argued that individuals with certain impairments should not be granted full moral status and therefore, by extension, should not be awarded the same inviolability as humans without cognitive impairments. In response, I argue that an overlooked social ability – the capacity to narrate – provides grounds for the full moral status of individuals with severe cognitive impairments, and thus provides a defense and support for individuals with such "disabilities" to play a robust role in moral action and contribution to human living.